A new species and a new natural hybrid of Laelia (Orchidaceae) from Oaxaca, Mexico - Salazar, Gerardo A.; Jiménez-Machorro, Rolando; Huerta, Héctor M.; Hágsater, Eric (Phytotaxa, 2014)
A new species, Laelia halbingeriana, and a new natural hybrid, Laelia ×oaxacana, both from the Sierra Madre Oriental in northern Oaxaca, Mexico, are described and illustrated. Laelia halbingeriana is similar to L. superbiens, from Chiapas through Nicaragua, differing in the proportionately shorter, stouter pseudobulbs, low, entire, distally white keels of the labellum and obscurely bilobed anther. Laelia ×oaxacana is applied to a hybrid swarm between L. halbingeriana and sympatric L. anceps. The hybrid can be distinguished from L. halbingeriana by the distichous (vs. spiral) raceme and the spreading petals oriented vertically (vs. distinctly arcuate and oriented horizontally), and from L. anceps in the stouter plants with two-leaved pseudobulbs and the proportionately narrower, waved sepals and petals.